Cost-effective device for split vent trap organic compounds from gas chromatograph - Pinsrithong, Pisamai; Pinsrithong, Sakchaibordee (Health Science, Science and Technology Reviews, 2020)
Since, the problem of volatile organic matter split vent from the gas chromatograph, affecting the health of workers, lead to the invention of adsorption device for volatile organic matter that split from front and back of gas chromatograph, using in laboratories. The adsorption device includes a syringe containing the used activated carbon. In this work the device was studied under actual working conditions. Absorption efficiency of the device for heptane and dichloromethane adsorption were found as 99.51% - 99.98% and 96.68% - 99.35% respectively. The number of times that it can be reused is 10 with 7 months life time each. Moreover, the device is cheaper than commercial split vent trap 18 times. Therefore, it is appropriate to use this device in laboratories for worker safety.